ASSESSMENT OF THE OCCLUSAL RELATIONS NATURE AT THE STAGES OF ORTHOPEDIC REHABILITATION OF PERSONS WITH PERIODONTAL TISSUE DISEASES COMPLICATED BY DENTITION DEFECTS - О.V. Bida; О.V. Bida (Український стоматологічний альманах)
Resume. According to epidemiological studies, there is still an increased prevalence of periodontal disease among the population of different regions of the world, with increasing intensity and aggressiveness. Long-term chronic generalized lesions of recurrent and progressive inflammatory-dystrophic process lead to the destruction of alveolar processes, pathological mobility of teeth, tooth loss and dentofacial dysfunctions. One of the most characteristic symptoms of generalized periodontitis is the presence of traumatic occlusion. Depending on the degree of pathological changes in periodontal tissues, the size and topography of dentition defects, the replacement of dentition pathologies should be planned by splint-type orthopedic structures and computerized analysis of occlusal relationships with T-Scan III system.